MENINGKATKAN PENGUASAAN VOCABULARIES SISWA MELALUI LAGU – LAGU BAHASA INGGRIS DI KELAS VIIl-2 SMP NEGERI 2 MARDINGDING SEMESTER GANJIL TAHUN PELAJARAN 2015/2016 - Jendakita Br Sinulingga (elt, 2020)
ABSTRACTThis study aims to improve student learning outcomes in learning English by using themedia of English songs. The subjects of this study were 27 students of class VIII-2 ofSMP Negeri 2 Mardingding, Mardingding District, Karo Regency, consisting of 11 malestudents and 16 female students. The research method applied is a classroom actionresearch method. Through two learning cycles, each cycle is carried out with planning,implementation, observation and reflection activities. Based on the results of dataanalysis, it is known that by using the media of English songs in English lessons in classVIII-2 of SMP Negeri 2 Mardingding, Mardingding District, Karo Regency, 2015/2016Academic Year, mastery of students' vocabularies has increased from Cycle First toCycle Second. Mastery of students' vocabularies in the first cycle obtained an averagescore of 30 with the percentage of the acquisition score of the total score of 30% and thisis in the very poor category (not good). And far from KKM (70). In the second cycle ofvocabulary mastery students obtained an average score of 80 with a percentage of theacquisition score of a total score of 80% and this is in a good category and hasexceeded KKM (70). So, the increase in students' vocabularies mastery from cycle I tocycle II was 50%, while student learning outcomes after using English songs as media inlearning English also increased. Likewise, the number of students who have completedthe KKM has reached the indicators of success, where the standard is 80%, while theacquisition is 96%. Keywords: Using English songs improves mastery of English vocabularies